Nanoparticle display of prefusion coronavirus spike elicits S1-focused cross-reactive antibody response against diverse coronavirus subgenera - Hutchinson, Geoffrey B.; Abiona, Olubukola M.; Ziwawo, Cynthia T.; Werner, Anne P.; Ellis, Daniel; Tsybovsky, Yaroslav; Leist, Sarah R.; Palandjian, Charis; West, Ande; Fritch, Ethan J.; Wang, Nianshuang; Wrapp, Daniel; et al. (Nature communications, 2023)
Multivalent antigen display is a fast-growing area of interest toward broadly protective vaccines. Current nanoparticle-based vaccine candidates demonstrate the ability to confer antibody-mediated immunity against divergent strains of notably mutable viruses. In coronaviruses, this work is predominantly aimed at targeting conserved epitopes of the receptor binding domain. However, targeting conserved non-RBD epitopes could limit the potential for antigenic escape. To explore new potential targets, we engineered protein nanoparticles displaying coronavirus prefusion-stabilized spike (CoV_S-2P) trimers derived from MERS-CoV, SARS-CoV-1, SARS-CoV-2, hCoV-HKU1, and hCoV-OC43 and assessed their immunogenicity in female mice. Monotypic SARS-1 nanoparticles elicit cross-neutralizing antibodies against MERS-CoV and protect against MERS-CoV challenge. MERS and SARS nanoparticles elicit S1-focused antibodies, revealing a conserved site on the S N-terminal domain. Moreover, mosaic nanoparticles co-displaying distinct CoV_S-2P trimers elicit antibody responses to distant cross-group antigens and protect male and female mice against MERS-CoV challenge. Our findings will inform further efforts toward the development of pan-coronavirus vaccines. Most current anti-coronavirus nanoparticle vaccines target epitopes within the RBD. Here, the authors developed nanoparticles displaying an array of spike fusion proteins derived from various coronaviruses and show that immunizing mice with these vaccines elicits broad and potent cross-reactive antibodies.